자폐 범주성 장애 아동의 눈맞춤과 얼굴표정읽기 기능향상을 위한 행동 중재용 로봇시스템 - 윤상석; 김혁수; 최종석; 박성기 (한국로봇학회, 2015)
In this paper, we propose and examine the feasibility of the robot-assisted behavioral intervention system so as to strengthen positive response of the children with autism spectrum disorder (ASD) for learning social skills. Based on well-known behavioral treatment protocols, the robot offers therapeutic training elements of eye contact and emotion reading respectively in child-robot interaction, and it subsequently accomplishes pre-allocated meaningful acts by estimating the level of children’s reactivity from reliable recognition modules, as a coping strategy. Furthermore, for the purpose of labor saving and attracting children’s interest, we implemented the robotic stimulation configuration with semi-autonomous actions capable of inducing intimacy and tension to children in instructional trials. From these configurations, by evaluating the ability of recognizing human activity as well as by showing improved reactivity for social training, we verified that the proposed system has some positive effects on social development, targeted for preschoolers who have a high functioning level.